2020
DOI: 10.1177/1938965519892902
|View full text |Cite
|
Sign up to set email alerts
|

Company Response to Negative Online Reviews: The Effects of Procedural Justice, Interactional Justice, and Social Presence

Abstract: This research investigates how potential customers evaluate a company response to negative online reviews. Integrating the literature on perceived justice in service recovery, social presence in online communications, and signaling in trust formation process, this research examines the effects of procedural justice, interactional justice, and social presence in the company’s response to negative online reviews on potential customers’ trust and purchase intentions toward a company. A 2 × 2 × 2 between-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 93 publications
(151 reference statements)
0
20
1
Order By: Relevance
“…However, service failures can range from the ordinary cases to more major cases (Goodwin and Ross, 1992;Berry and Parasuraman, 1991;Gilly and Gelb, 1982) and perceived severity of cases has been identified as the mediating factor of an effective service recovery (McCollough et al, 2000;Smith et al, 1999;Limbrick, 1993;Zeithaml et al, 1993;Bell and Ridge, 1992). It is also found that service failure severity has a significant strong effect on service recovery satisfaction (Olson and Ro, 2020).…”
Section: Developing Service Failure Severity Versus Perceived Justice Frameworkmentioning
confidence: 89%
See 1 more Smart Citation
“…However, service failures can range from the ordinary cases to more major cases (Goodwin and Ross, 1992;Berry and Parasuraman, 1991;Gilly and Gelb, 1982) and perceived severity of cases has been identified as the mediating factor of an effective service recovery (McCollough et al, 2000;Smith et al, 1999;Limbrick, 1993;Zeithaml et al, 1993;Bell and Ridge, 1992). It is also found that service failure severity has a significant strong effect on service recovery satisfaction (Olson and Ro, 2020).…”
Section: Developing Service Failure Severity Versus Perceived Justice Frameworkmentioning
confidence: 89%
“…Prior research suggests that company's service recovery effort by responding to negative online customer reviews (OCRs) signals a commitment to improve service quality and affects potential customer's trust toward company credibility; subsequently it influences their purchase intention (Olson and Ro, 2020;Sparks and Bradley, 2014;Pantelidis, 2010;Ye et al, 2008). While the company in the hospitality and service industry is becoming aware of the importance to manage negative OCRs, these companies are still unsure how to best respond to customer complaints (Sparks et al, 2016;Schaefers and Schamari, 2016;Sparks and Bradley, 2014;Xie et al, 2014).…”
Section: Introduction "Dear Managermentioning
confidence: 99%
“…Five of those articles involved retrospective analysis of actual online posts where we learned about biases in posting (Han & Anderson, 2020); differences in organic versus solicited posts (Litvin & Sobel, 2019); how managers have responded to customer posts (Xie et al, 2017); factors leading to positive TripAdvisor scores (Radojevic et al, 2017) and textual elements common in online reviews (Duan et al, 2016). There has also been a stream of research involving the creation of fictitious online reviews or situations evaluated by students or online panels that have investigated issues such as expectations regarding online review posts (Zhang et al, 2020); reactions to customer online complaints (Kim & Baker, 2020); the role of micro-celebrity or influencer (Zhang et al, 2019); how different elements in online reviewers affect consumers (Olson & Ro, 2020); how valence and uniqueness in reviews influence consumers (Chark et al, 2019); determining whether managers ought to react to negative reviews (Rose & Blodgett, 2016); how social media embedded in channels influences behavior (Aluri et al, 2016); and in a survey-type design, how social word-of-mouth influences loyalty (Raab et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There has also been a stream of research involving the creation of fictitious online reviews or situations evaluated by students or online panels that have investigated issues such as expectations regarding online review posts (Zhang et al, 2020); reactions to customer online complaints (Kim & Baker, 2020); the role of micro-celebrity or influencer (Zhang et al, 2019); how different elements in online reviewers affect consumers (Olson & Ro, 2020); how valence and uniqueness in reviews influence consumers (Chark et al, 2019); determining whether managers ought to react to negative reviews (Rose & Blodgett, 2016); how social media embedded in channels influences behavior (Aluri et al, 2016); and in a survey-type design, how social word-of-mouth influences loyalty (Raab et al, 2016). What has not been addressed in the hospitality literature, and the focus of our work, is on how social media information can be used by an organization as part of its experience management process.…”
Section: Conceptual Implicationsmentioning
confidence: 99%
“…Fourth, the current literature largely focuses on management responses of negative online reviews as recovery actions (Olson & Ro, 2020; Xie et al, 2014). Limited research examines the impact of management responses in situations in which customers post their general service experience without any intention of spreading negative word-of-mouth.…”
Section: Discussionmentioning
confidence: 99%